A review of sheep pox and goat pox: perspective of their control and eradication in Iran (Journal of Advanced Veterinary and Animal Research, 2015)
Sheep pox and goat pox (SGP) of small ruminants are most severing pox diseases of domestic animals, and  they  have  a  very  important  role  in  agricultural economy. Thereby, SGP are included in the notifiable diseases of Office International des Epizooties (OIE). Time  and  place  distributions  of  these  diseases  are relatively  stable  worldwide.  Transportation  of infected  animals  could  spread  these  viruses  to  the new  areas.  In  most  countries  in  which  capripox  are enzootic,  vaccination  and  bio-security  are  the  only two  main  control  measures.  SGP  control  programs have been commenced about 50 years ago in Iran, and there is a good situation for eradication of it. In this review,  readers  can  find  latest  information  in  some essential  aspects  of  etiology,  distribution, transmission,  and  control  of  the  diseases.  Besides, current  situation  of  the  disease  in  Iran  has  been described,  which  perhaps  are  similar  to  the  other endemic areas in the world. http://dx.doi.org/10.5455/javar.2015.b117